FRI0259 Increased risk of osteoporosis and fracture in women with systemic sclerosis: A comparative study to rheumatoid arthritis and healthy controls. (23rd January 2014) - Avouac, J.; Koumakis, E.; Toth, E.; Meunier, M.; Maury, E.; Cormier, C.; Kahan, A.; Allanore, Y.
Abstract : Objectives: To investigate whether women with SSc have increased risk of OP and fractures compared to a "high risk" population with rheumatoid arthritis (RA) and also healthy controls. Methods: Cross-sectional study with successive inclusion of age-matched healthy, SSc, and RA women on a 18-month period. Risk factors for OP and fractures, including age, menopausal status, calcium/vitamin D intake, family history, comorbidity and steroid use, were collected for all patients. Bone mineral density (BMD) was assessed at AP lumbar spine (L1-L4), femoral neck, and total hip region with DXA Prodigy (GE-Lunar) or QDR4500 (Hologic). We included 71 women with SSc (62±12 years old), 139 with RA (61±11 years old) and 227 healthy controls (60±8 years old). The mean ± standard deviation, SD, disease duration of SSc and RA patients was 10±9 and 18±13 years respectively (p<0.001). SSc and RA patients were more likely to receive vitamin D (69% and 76% vs. 25%, p<0.001 for both comparisons) and calcium (48% and 72% vs. 14%, p<0.001 for both comparisons) supplementation than healthy controls. RA Patients were more likely to receive calcium supplementation (100 (72%) vs. 34 (48%), p<0.001) and corticosteroids (129 (93%) vs. 41 (58%), p<0.001) than SSc patients. Cumulative dose of corticosteroids and CRP were significantly higher in patients with RA than SSc (39554±29661 mg vs. 19392±19333 mg, p<0.0001 and 12±16 mg/l vs. 7±7.9 mg/l, p=0.01). Results: The point prevalence of OP (T-score <-2.5) was similar in SSc and RA (30% and 32% respectively), and was for both significantly higher than in healthy controls (11%, p<0.001 vs. SSc and RA). The frequency of lumbar spine and total hip OP did not differ between SSc and RA. The point prevalence of fractures was 35% and 33% in SSc and RA, respectively (p=NS) and 10% in healthy controls (p<0.001 vs. SSc and RA). The frequency of vertebral (25% and 19%) and non-vertebral fracture (23% and 22%) did not differ between SSc and RA. Multivariate analysis identified disease duration as the only risk factor of OP in SSc (odds ratio, OR: 1.21, 95% confidence interval, CI: 1.02-1.30). There was no association between OP and corticosteroid intake, cumulative dose of corticosteroids, systemic inflammation (CRP >10mg/l) or any SSc feature Age (OR: 1.21, 95% CI 1.03-1.38) and low 25(OH)D levels (OR: 6.02, 95% CI 1.46-24.78) were recognized as risk factors of fracture in SSc. In comparison, age (OR: 1.12, 95% CI 1.02-1.26) and corticosteroid treatment (OR: 3.21, 95% CI: 1.12-10.44) were independently associated with OP in RA. Cumulative dose of corticosteroids negatively correlated with BMD measured at lumbar spine (r=0.38, p=0.01) and total hip (r=0.49, p=0.008) in RA patients. Multivariate analysis confirmed age (OR: 1.09, 95% CI 1.03-1.18), OP (OR: 3.22, 95% CI 1.18-8.75) and low 25(OH)D levels (OR: 4.31, 95% CI 1.29-14.41) as independent risk factors of fractures in RA. Conclusions: The prevalence of OP and fracture in SSc was increased compared to healthy women and reached the high prevalence associated with RA. Age and vitamin D deficiency were identified as risk factors of fracture in SSc. Thus, increasing the awareness and performance of BMD measurements together with vitamin D supply in patients with SSc is warranted. Disclosure of Interest: None Declared